Role of the Kölliker-Fuse nucleus in cardiovascular responses to hypoxia and baroreceptor activation in anesthetized rats - Mirzaei-Damabi, Nafiseh (Bioimpacts, 2020)
[Image: see text] Introduction: Parabrachial Kölliker-Fuse (KF) complex, located in dorsolateral part of the pons, is involved in the respiratory control, however, its role in the baroreflex and chemoreflex responses has not been established yet. This study was performed to test the contribution of the KF to chemoreflex and baroreflex and the effect of microinjection of a reversible synaptic blocker (Cocl(2)) into the KF in urethane anesthetized rats. Methods: Activation of chemoreflex was induced by systemic hypoxia caused by N2 breathing for 30 seconds "hypoxic- hypoxia methods" and baroreflex was evoked by intravenous injection (i.v.) of phenylephrine (Phe, 20 µg /kg/0.05–0.1 mL). N2 induced generalized vasodilatation followed by tachycardia reflex and Phe evoked vasoconstriction followed by bradycardia. Results: Microinjection of Cocl(2) (5 mM/100 nL/side) produced no significant changes in the Phe-induced hypertension and bradycardia, whereas the cardiovascular effect of N2 was significantly attenuated by the injection of CoCl(2) to the KF. Conclusion: The KF played no significant role in the baroreflex, but could account for cardiovascular chemoreflex in urethane anesthetized rats.